Contrasting effects of agriculture and urbanisation on bird and reptile communities in a Mediterranean delta (Gediz Delta, Türkiye) - Arslan, Dilara; Gaget, Elie; Çiçek, Kerim; Olivier, Anthony; Galewski, Thomas; Döndüren, Ömer; Guelmami, Anis; Ernoul, Lisa; Béchet, Arnaud (Springer Science and Business Media LLC, 2025)
Background
Wetlands have been some of the most destroyed ecosystems over the last century, with important land-use changes resulting from agricultural, industrial, and urban development. Gediz Delta is a large wetland on the Aegean coast of Western Türkiye with natural areas affected by conversion to agriculture and urban developments from the Izmir metropolis. We assessed the effects of landscape type (natural, agricultural, and urban) on the composition of breeding bird (90 species) and reptile (14 species) communities in the Gediz Delta between 2019 and 2021. We used generalized linear models to estimate the effect of landscape types on community indexes and joint species distribution models to assess how species-specific habitat preferences explained their responses to landscape type.
Results
Our results show that bird and reptile community compositions were impacted differently depending on landscape type. Landscape type significantly affected bird abundance and Shannon equality indices but had no significant effect on bird and reptile species richness. Natural landscapes accommodated higher bird abundance and lower diversity indexes than the other two landscapes. On the other hand, we found that urban and agricultural landscapes accommodated more generalist species than natural ones. Natural landscapes were preferred by Marine & Coastal and Inland wetland bird specialists and reptiles relying on Mediterranean Habitats. Overall, these results suggest that community composition encountered in different landscape types is explained by species’ habitat specializations.
Conclusions
We highlight the critical importance of natural landscapes for conserving specialist species within the Delta while showing the potential of agricultural areas for a few freshwater reptile species. These results imply that the Gediz Delta would benefit from biodiversity conservation planning to enhance the protection of natural habitats and mitigate the negative impacts of agricultural and urban development on bird and reptile populations.